Reviews of recent publications (Studies in 20th & 21st Century Literature, 2003)
Aizenberg, Edna. Parricide on the Pampa? A New Study and Translation of Alberto Gerchunoffs "Los gauchos judíos" by Jan Mennell Emerson, Caryl, ed. Critical Essays on Mikhail Bakhtin by Michael Barry Finney, Gail. Christa Wolf by Stephen Brockmann Hoeg, Jerry. Science, Technology, and Latin American Narrative in the Twentieth Century and Beyond by Paul Fallon Mendez-Ramirez, Hugo. Neruda's Ekphrastic Experience: Mural Art and Canto general by Agustin Boyer Perriam, Chris, Michael Thompson, Susan Frenk, and Vanessa Knights. A New History of Spanish Writing: 1939 to the 1990s by William Sherzer Soto, Francisco. Reinaldo Arenas by Marina Llorente
Keywords: Edna Aizenberg; Parricide on the Pampa? A New Study and Translation of Alberto Gerchunoffs Los gauchos judíos; Jan Mennell; Caryl Emerson; Critical Essays on Mikhail Bakhtin; Michael Barry; Gail Finney; Christa Wolf; Stephen Brockmann; Jerry Hoeg; Science Technology and Latin American Narrative in the Twentieth Century and Beyond; Paul Fallon; Hugo Mendez-Ramirez; Neruda' s Ekphrastic Experience: Mural Art and Canto general; Agustin Boyer; Chris Perriam; Michael Thompson; Susan Frenk; Vanessa Knight; A New History of Spanish Writing: 1939 to the 1990s; William Sherzer; Francisco Soto; Reinaldo Arenas; Marina Llorente